Soil rehabilitation shaped different patterns of bacterial and archaeal community in AMD-irrigated paddy soil. (January 2021) - Wang, Han; Zeng, Yufei; Guo, Chuling; Zheng, Xiongkai; Ding, Cui; Lu, Guining; Dang, Zhi
Abstract: Microorganisms are essential for soil rehabilitation and long-term sustainability of established plants. However, the recovery process of microorganisms in AMD-irrigated paddy soil is poorly understood at present. To verify this, we sampled AMD-irrigated paddy soils before at different rehabilitation stages by characterizing bacteria and archaea community from a chronosequence of AMD-irrigated rehabilitation to pre-disturbance levels from references sites. Next-generation sequencing is used to describe shifts in diversity and taxonomic composition of bacterial and archaeal. Co-occurrence networks are constructed to reveal potential microbial interaction patterns. The result showed bacterial community followed an observable taxonomic transition overtimes, with community structure becoming more similar to that of unmined reference sites. But the archaeal community only showed a seasonal change, which may hint that the archaeal community needs more time in rehabilitation. Both bacterial and archaeal community composition changes were apparent at high taxonomic levels, bacterial communities become dominated by Proteobacteria phylum, and archaeal community was dominated by Crenarchaeota, we proposed the possible reason is bacterial community were mainly derived by soil pH while the archaeal community was impacted by heavy metal. The bacterial co-occurrence networks increased in complexity during succession, improving the community's resistance to environmental disturbance, while the archaeal did not change monotonically with time. This study highlights the distinct recovery pattern of the bacterial and archaeal community during AMD-irrigated paddy soil rehabilitation, which provides a deep understanding of their role in paddy soil, and subsequent harnessing of their potential to pave the way in future rehabilitation strategies for mined sites. Graphical abstract: Image 1 Highlights: The bacterial community structure becoming more similar to unmined reference sites during rehabilitation. Both bacterial and archaeal community composition changes were apparent at high taxonomic levels. Bacterial community was mainly derived by soil pH while the archaeal community was impacted by heavy metal. Only the co-occurrence networks of bacterial community was increased in complexity during succession.